Meta-Analysis the Effect of Asthma Comorbidity on the Mortality of COVID-19 Patients - Siti Mar'atul Munawaroh; Hanung Prasetya; Bhisma Murti (Journal of Epidemiology and Public Health, 2021)
Background: COVID-19 is an infectious disease that spread throughout the world in December 2019. The risk factors for mortality of COVID-19 patients depend on comorbid diseases. Most of the comorbid diseases associated with COVID-19 deaths consist of hypertension, diabetes, obesity, cardiovascular disease, chronic obstructive pulmonary disease, chronic kidney disease, and asthma. This study aims to analyze the effect of comorbid asthma on mortality in COVID-19 patients.Subjects and Method: This research is a meta-analysis study using PRISMA flowchart guidelines. The article search process was carried out between 2020-2021 using databases from PubMed, Google Scholar, and Scopus. Based on the database, there were 15 articles that met the inclusion criteria. The analysis was carried out using the RevMan 5.3 software.Results: The 15 articles reviewed in the meta-analysis showed that comorbid asthma increased the mortality risk of COVID-19 patients and was statistically significant (aOR = 1.18; 95% CI = 1.02 to 1.36; p = 0.030).Conclusion: Asthma comorbidities increase the mortality of COVID-19 patients.Keywords: Asthma, mortality, COVID-19, SARS-CoV 2Correspondence: